2004
DOI: 10.1111/j.1349-7006.2004.tb03184.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation profiling of 30 genes in human malignant melanoma

Abstract: Aberrant methylation and demethylation of promoter CpG islands lead to silencing of tumor-suppressor genes and abnormal expression of normally methylated genes, respectively. Here, we analyzed human melanomas for their methylation and demethylation profiles. Methylation status of core regions in promoter CpG islands was examined for 20 (candidate) tumor-suppressor genes, 4 genes that are not considered as tumor-suppressors, but are frequently silenced in human cancers, and 6 normally methylated melanoma antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 32 publications
10
75
0
2
Order By: Relevance
“…It should be noted that similarly to the samples reported by Furuta et al, (Furuta et al, 2004), none of our cell lines showed PTEN promoter hypermethylation, which has been shown or suggested in some melanomas (Zhou et al, 2000;Mirmohammadsadegh et al, 2006). Similarly, using the criterion of a minimum 2-fold change after drug treatment, we have no evidence that the p14ARF promoter is methylated in any of the 7 cell lines tested in which the gene is not homozygously deleted.…”
Section: Discussionmentioning
confidence: 55%
“…It should be noted that similarly to the samples reported by Furuta et al, (Furuta et al, 2004), none of our cell lines showed PTEN promoter hypermethylation, which has been shown or suggested in some melanomas (Zhou et al, 2000;Mirmohammadsadegh et al, 2006). Similarly, using the criterion of a minimum 2-fold change after drug treatment, we have no evidence that the p14ARF promoter is methylated in any of the 7 cell lines tested in which the gene is not homozygously deleted.…”
Section: Discussionmentioning
confidence: 55%
“…as found in the pro-tumor niche), MAGE protein expression can be induced. 15 Expression of MAGE-A family proteins has been reported for more than half of all human cancers. 16 One of its members, MAGE-A6, is expressed in more than 60% of melanomas, 17 30% of renal cell carcinomas, 18 and by numerous other malignancies, such as breast, esophageal, head and neck, bladder, and lung carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…These cell lines were selected because they had different origins and frequencies of methylation 19 : HMV-I, MeWo and WM-115 originated from a primary lesion of genital mucosa, a metastatic lesion of a lymph node, and a primary skin lesion, respectively, and exhibited frequent, infrequent and intermediately frequent gene silencing, respectively.…”
mentioning
confidence: 99%